FROM SOCRATES TO TAYLOR, AN EVALUATION OVER MANAGEMENT THOUGHT (Third Sector Social Economic Review, 2022)
Although it is accepted that management science started at the beginning of the 20th century and especially with the work of Frederick Taylor, management thought and practices date back thousands of years. The study argues that a management approach, albeit simple, has emerged since people began to live in communities. The transformation of communities into cities, cities into states and great civilizations necessitated the development of a systematic management approach. Many thinkers have worked on this subject from the period when history was recorded to the present, and noted different management views and understandings.""Scientific Management"" of F. Taylor and ""Management Principles Approach"" of Henri Fayol were recorded as the birth of management science. However, many thinkers from Socrates to Sun Tzu, from Aristoteles to Adam Smith had similar thoughts centuries ago. This study aims to reveal the similarities between these thinkers’ works and scientific management. The study does not intend to bring up all the works of philosophers or thinkers who have spoken about management. It aims to relate management theory to its past through 6 thinkers’ works that affected the history of management and organization.
Keywords: Pioneers of Management Theory; Development of Management Thought; Organization Theory; Taylorism; Management Principles